2019
DOI: 10.1016/j.compositesb.2019.107056
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrothermal ageing on the fatigue behaviour of a unidirectional flax-epoxy laminate

Abstract: Although the research and development in plant fibre composites is growing rapidly, these materials still require specific considerations before being adopted by industry in structural applications. One of the main issue is related to their durability. The objective of this study is to investigate the influence of hydrothermal ageing on the fatigue behaviour of an unidirectional flax-epoxy laminated composite by implementing the fatigue tests in a water bath. Results show that while the quasi-static strength a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Finally, these results show that, for a high σ max value, the fatigue life is higher for the Ambient conditioning than for the Wet or the Wet/dry ones, but for a low σ max value, the fatigue life is higher for the Wet conditioning than for the Ambient or the Wet/dry ones. This lower fatigue sensitivity for specimens tested in humid environment compared to the one of specimens tested in ambient conditions has also recently been shown for unidirectional flax/epoxy composite [54]. In the present study, it is also demonstrated that the Wet/dry conditioning exhibits a specific behaviour, with the same fatigue sensitivity as the one of Ambient samples and the same tensile strength as the one of Wet samples.…”
Section: Wöhler Curvessupporting
confidence: 85%
“…Finally, these results show that, for a high σ max value, the fatigue life is higher for the Ambient conditioning than for the Wet or the Wet/dry ones, but for a low σ max value, the fatigue life is higher for the Wet conditioning than for the Ambient or the Wet/dry ones. This lower fatigue sensitivity for specimens tested in humid environment compared to the one of specimens tested in ambient conditions has also recently been shown for unidirectional flax/epoxy composite [54]. In the present study, it is also demonstrated that the Wet/dry conditioning exhibits a specific behaviour, with the same fatigue sensitivity as the one of Ambient samples and the same tensile strength as the one of Wet samples.…”
Section: Wöhler Curvessupporting
confidence: 85%
“…Indeed, contrary to most petrosourced composites, PFCs are highly sensitive to hygrothermal conditions and their variation and/or cycling over time [13]. Their monotonic, fatigue and vibrational behaviours are reported to be significantly influenced by such parameters [8,9,[14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Complex behaviour is observed, including nonlinearities as well as strain hardening and strain-softening effects, depending on the mechanical loading and hygrothermal exposition combinations [9,17]. In contrast, the timedelayed behaviour has not been adequately investigated.…”
Section: Introductionmentioning
confidence: 99%
“…20 Additional studies on the fatigue performance and fatigue life of flax composites under stress-controlled amplitude can be found in the following references. 15,[21][22][23][24][25][26][27] Studies 4,[23][24][25][26] found that flax/epoxy composites exhibit unusual behavior in laminates with unidirectional plies, in which the modulus of the composite progressively increases, rather than decreases, with fatigue cycling. Mahboob et al 28,29 argued that these composites were immune to material degradation, even though there is physical microcracking and an increase in residual strain due to internal damage accumulation.…”
Section: Introductionmentioning
confidence: 99%